Megacolon due to Chronic Schistosomiasis: A Case Report and Review of Literature. (6th March 2019) - Alzahrani, Amer R.; Alawfi, Homoud; Almeman, Sara; Altayeb, Thamer; Al-Dorzi, Hasan M.
Abstract : Although Schistosoma infection in humans commonly involves the intestines, megacolon is a rare finding. We report a 47-year-old patient who was found to have chronic megacolon. After failing conservative management, he underwent extended hemicolectomy with colorectal anastomosis. The colon pathology revealed chronic schistosomiasis and Schistosoma serology was positive.